LINGUISTICS - Khoirul Huda (Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2018)
Linguistics is the scientific study of natural language and is one of the four subfield of anthropology. Linguistics encompasses a number of sub-fields. An important topical division is between the study of language structure (grammar) and the study of meaning ( semantics and pragmatics). Grammar encompasses morphology (the formation and composition of words ), syntax (the rules that determine how words combine into phrase and sentences) and phonology (the study of sound systems and abstract sound units). Part of linguistics are syntax, morphology, phonology, sociolinguistic and psycholinguistic.